Effects of fibroblast growth factor-10 on the secretions of transforming growth factor-alpha, platelet-derived growth factor-AB and vascular endothelial growth factor by normal adult human keratinocytes in culture - Sun, Xiao-qing (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2004)
OBJECTIVE: To evaluate the effect of fibroblast growth factor-10 (FGF-10) on the secretion of transforming growth factor-alpha (TGF-alpha), platelet-derived growth factor-AB (PDGF-AB) and vascular endothelial growth factor (VEGF) by human keratinocytes